Concepts of the Philosophy of Assumptions and its Theoretical Implications - Kmuníček, Vilém (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This paper aims to give an overview of my findings in the field of gnoseological and ontological certainty. I proposed a philosophy of assumptions. I will introduce some concepts, in particular the notion of an actual mental model, which points to the impossibility of bypassing the subject in cognitive activity. This also reflects the proposal to include in the methodological assumptions of science, the claim that reality is given to us in cognition only through the contents of consciousness. Finally, interpretations in terms of newly introduced concepts as virtual reality, functioning of artifacts, and truth are placed. The previous results of my cognitive findings were used to compile the overview. This inquiry is based on a lifetime of unsystematic reading and then selecting texts for the topic by a snowballing process. This is how my thought-conceptual system, a world view, was created, which I attempt to objectify in this way.